Small fruit breeding in Finland - Heimo Hiirsalmi (Scientific Agricultural Society of Finland, 1988)
In Finland, the breeding of small fruits has been focused on species belonging to the Ribes, Fragaria, Rubus, Vaccinium and Hippophaë genera. Of the blackcurrant, many local varieties have been brought under cultivation during this century, the most significant being ‘Brödtorp’ and ‘Melalahti’. The Department of Horticulture of the Agricultural Research Centre has, by means of intervariety crossings, developed selections combining high yield, upright growth and resistance to gooseberry mildew. A selection with greenberries, chosen from among the self-pollination progeny of the Swedish ‘Öjebyn’ variety, was released for cultivation in 1987, under the name ‘Vertti’. As to the gooseberry, the old Finnish varieties ‘Hinnnomäen keltainen’ and ‘Lepaanpunainen’ are still generally cultivated. In 1984, the Department of Horticulture released the late, cultivated strawberry variety ‘Hiku’, a very good cropper, for cultivation. It comes from the crossing ‘Senga Sengana’ x ‘Redgauntlet’. The most promising early selection, which this spring was released for cultivation under the name ‘Mari’, comes from the crossing ‘Pocahontas’ x ‘Lihama’. In 1986, the wood strawberry variety ‘Minja’ a result of the crossing Fragaria vesca x ‘Rügen’, was brought under cultivation. In the breeding of the raspberry, the Department of Horticulture has utilized the gene pools of wild raspberries; this has produced new selections with fairly good winter hardiness. This spring a variety named ‘Ville’, which was produced in the crossing of the Canadian ‘Ottawa’ and a Finnish wild raspberry strain, was introduced on the market. In addition, the raspberry has been crossed with the arctic bramble. By means of many crossings and back-crossings, the so-called nectar raspberry was developed, of which the variety ‘Heija’ was released for cultivation in 1975 and the variety ‘Heisa’ in 1981. Of the arctic bramble, two natural strains selected by the North Savo Research Station of the Agricultural Research Centre were brought under cultivation in 1972 ...